The Effect of Information Asymmetry and Business Diversification on Cost of Equity Capital - Nurul Intan Okci Pratiwi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2021)
This study aims to examine the effect of information asymmetry and business diversification on the cost of equity capital in mining companies listed in the Indonesia Stock Exchange with a sample of 14 companies for the 2017-2019 period. Data analysis used descriptive research with quantitative research methods in the form of secondary data. Information asymmetry is measured using the bid-ask spread and diversification is measured using the Herfindahl Index proxy while the cost of equity capital is measured using the Ohlson model. Hypothesis testing is carried out using multiple linear regression analysis to see how much influence information asymmetry and diversification have on the cost of equity capital. The result indicated that information asymmetry had a positive impact on the cost of equity capital and business diversification had a positive impact on the cost of equity capital.